2017
DOI: 10.1128/msphere.00210-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Microbiota of Older Adults Living in Nursing Homes and the Community

Abstract: The nose, throat, and skin over the subclavian and femoral veins are the body sites which harbor the bacteria which most commonly cause health care-associated infection. We assessed the effect of nursing home residence on the microbiota of these body sites in older adults. We found that the microbiota composition of the different body sites was similar between nursing home and community participants, but we identified differences in relative abundance levels. We found remarkable similarities in the bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…We deem, however, that the conclusion of this study would not be largely compromised due to the small size of the cohort, as the findings of this study were applicable to most of the participants, not only to the specific ones. Nonetheless, we could not rule out the possibility that the unique microbiome of bedridden older patients in this study might be because of the hospital environment and/or regional characteristics, although similar findings are reported in the different setting (9). Larger cohorts with multicenter setting will be required for future researches.…”
Section: Limitationsmentioning
confidence: 70%
See 3 more Smart Citations
“…We deem, however, that the conclusion of this study would not be largely compromised due to the small size of the cohort, as the findings of this study were applicable to most of the participants, not only to the specific ones. Nonetheless, we could not rule out the possibility that the unique microbiome of bedridden older patients in this study might be because of the hospital environment and/or regional characteristics, although similar findings are reported in the different setting (9). Larger cohorts with multicenter setting will be required for future researches.…”
Section: Limitationsmentioning
confidence: 70%
“…Roghmann et al have revealed similar findings (less commensals and more feces-related Proteus spp., Escherichia coli, and Enterococcus spp. on the femoral skin) in the ambulatory or wheelchair-aided older people of nursing homes (9). Although the study did not mention the use of diapers, it can be speculated that the gut-related bacteria on the skin of hospitalized older patients increases even in the regions where the diaper is not directly attached.…”
Section: Skin Dysbiosis In Bedridden Older Patientsmentioning
confidence: 90%
See 2 more Smart Citations
“…Following DNA extraction, the V3-V4 hypervariable region of the 16S rRNA gene was amplified by polymerase chain reaction and sequenced using the Illumina MiSeq platform (300 base pairs, paired-end reads) as previously described. 18,19 …”
Section: Methodsmentioning
confidence: 99%